Improvement of P.E.T delivery system for blow molding system / Mohd Norizwan Mat Salleh - Mat Salleh, Mohd Norizwan (2007)
The purpose of this study is to compare between the current mechanism and the purposed of new improved mechanism system for Polyethylene Terephthalate (PET) delivery system in bottle manufacturing industries. The current mechanism is conventional method which is using man power for delivery. Therefore, the new mechanism will change to modern method which is using centralize method consists of new redesign component and delivery systems. The comparison is based on the reduction in terms of wastage, cost consumption, workforce utilization and also efficiency of the machine. In order to get the results, current condition was analyzed and comparison has been done with new mechanism of PET delivery for stretch blow molding system. Some recommendation has been proposed to be reviewed by the company to be implemented in future.